The impact of Glucose and Sodium Chloride on the Biofilm Formation of Pseudomonas aeruginosa & Staphylococcus aureus - A. Mahdi, Estabraq; B. Al-Shaibani, Abdulwahid; S. Zbar, Nedhaal (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2020)
The aim of this research is to evaluate the effect of glucose and sodium chloride on biofilm formation by bacteria causing wound infection. For this purpose, 1% and 2% concentration of each of glucose and sodium chloride were used to test the biofilm formation potential of Staphylococcus aureus and Pseudomonas aeruginosa, which were the most common abundant bacteria that cause infection by biofilm. Each of the concentrations was kept in contact with the pathogenic bacteria for 24 hours. After the period of incubation, the concentration of 1% of glucose enhanced moderate biofilm formation capacity for (66% and 80%) on both bacteria respectively. The concentration of 2% glucose, on the other hand, led to a weak biofilm for 33% and 20% on both bacteria isolates respectively. In respect to the effect of sodium chloride, no isolate was able to form neither moderate nor strong biofilms. Nonetheless, all isolates succeeded in forming weak biofilms at 2% sodium chloride, while treatment with a concentration of 1% sodium chloride led to inhibited biofilm formation for 43% of isolates. Besides, Pseudomonas aeruginosa isolates were able to form moderate biofilms in the presence of 1% concentration of glucose, and weak producers in the presence of 2% glucose concentration. The isolates succeeded in forming strong biofilms at both 1% and 2% sodium chloride.